Tooth extraction: Pattern and etiology from extreme Northwestern Nigeria - Taiwo, Abdurrazaq Olanrewaju (Eur J Dent, 2017)
OBJECTIVE: Tooth extraction is a commonly performed procedure in dental clinics. It has been shown that the reasons for and pattern of tooth extraction vary across geographical regions. Few reports on the pattern of extraction among a semi-urban populace exist. To the best of our knowledge, there is no study on the pattern and reasons for tooth mortality from Sokoto, Northwestern Nigeria, which is a semi-urban region. MATERIALS AND METHODS: A review of the records of patients that had tooth extraction at our center between January 2009 and January 2016, was done. Data such as the age, gender, type of tooth extracted, and reasons for extraction were retrieved and analyzed. Cross tabulations for age and gender were also made. The level of statistical significance was set at P < 0.05. RESULTS: A total of 1167 extractions were performed in 984 patients. An age range of 18–107 years with a mean (±standard deviation) of 34.8 (13.3) was observed. Most of the patients were in the 21–30 years age group accounting for 35.7% of cases. Dental caries and its sequelae (DCS) (631, 54.1%) were the most common reasons for extraction, followed by periodontal disease (192, 16.5%). The difference in proportions of reasons for tooth extraction between the gender was statistically significant (P = 0.02; df = 24). The difference in the reasons for extraction among the age groups was statistically significant (P < 0.001; df = 132). CONCLUSION: DCS along with periodontal disease were the major reasons for extractions. These are largely preventable causes of tooth extraction; therefore, there is a need for commencement of far-reaching preventative actions.